Med teorijo in prakso - Franca, Valentina (Delavci in delodajalci, 2018)
Because of constant technological development the need for upgrading knowledge and obtaining new skills and competences is increasingly more intense, making the agreements between employers and unions about this issue highly relevant. The analysis of 26 sector collective agreements has shown that there is still considerable potential for joint cooperation in recognizing the needs and planning the development of skills and competences, inclusion in lifelong learning and provision of funds. Likewise, it would be advisable to develop a range of incentives for new knowledge as a form of motivation of workers and to arrange mutual relations in cases of education and training at the initiative or in the interest of a worker.
Keywords: delovna razmerja; izobraževanje; kolektivne pogodbe; usposabljanje; vseživljenjsko učenje